Realistic Mathematics Education and REACT Strategy in Context Mathematical Connections - Hasbi, Muhammad; Fitri, Fitri (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study aims to describe the process of developing and producing high-quality, realistic mathematics learning devices using the REACT strategy at the junior high school level and their effectiveness in training students' mathematical connection skills. This type of research is known as development research. The learning devices developed in this study are the Mathematics Connection Ability Tests. We developed the test using the 4-D development model, which consists of four stages: define, design, develop, and disseminate. The research subjects for the trial class were 35 students of class VIII-A, and the research subjects for the implementation class were 35 students of class VIII-B. This study used descriptive analysis. The results showed that the tests developed were of excellent quality because they met the criteria of valid, practical, and effective. In addition, realistic mathematics learning with the REACT strategy effectively trains students' mathematical connection skills. This is evident in the aspects of learning quality, the appropriateness of the learning level, the use of incentives, and the amount of time allocated, all of which align with the planning outlined in the learning implementation plan. Furthermore, realistic mathematics learning and the REACT strategy effectively enhance students' mathematical connection skills.